Sex differences in long-term outcomes of patients with percutaneous coronary intervention: the Armenian experience - Yeva Sahakyan; Michael E. Thompson; Lusine Abrahamyan (PAGEPress Publications, 2013)
The present study aimed at assessing sex differences in perioperative characteristics and 3-year event-free survival from major adverse cardiac and cerebrovascular events (MACCE) in patients with percutaneous coronary intervention (PCI) in Armenia. The study utilized an observational, retrospective cohort design enrolling patients who underwent PCI from 2006 to 2008 at a single center in Yerevan, Armenia. Major adverse cardiac and cerebrovascular events included all-cause mortality, myocardial infarction (MI), repeat revascularization, or stroke/transient ischemic attack. Among 485 participants included in the analysis, 419 (86%) were men. Women were older, more hypertensive, more obese, and had significantly higher rates of diabetes. At the end of follow-up, the incidence of MACCE was 37% for men and 33% for women (P=0.9). Based on the results from the adjusted Cox proportional hazards model, the independent predictors of MACCE included acute MI [hazard ratio (HR)=1.43, 95% confidence interval (CI): 1.02-2.00], arrhythmia (HR=1.64, 95% CI: 1.07-2.50), sex (HR=2.46, 95% CI: 1.08- 5.61), diabetes (HR=5.65, 95% CI: 2.14-14.95), and the interaction between sex and diabetes (HR=0.16; 95% CI: 0.05-0.47). Among diabetic patients, men had better event-free survival from MACCE (HR=0.40, 95% CI: 0.19-0.85) than women, whereas in patients without diabetes men had worse outcomes than women (95% CI: 1.08-5.62). In Armenia, the baseline profile of women undergoing PCI differed considerably from that of men. In patients with diabetes, women had worse outcomes at long-term follow-up, while the opposite was noted in patients without diabetes.